1996
DOI: 10.1136/bmj.313.7054.400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sports sponsorship by tobacco companies on children's experimentation with tobacco

Abstract: Tobacco companies often seem to direct their advertising campaigns at adolescents-for example, the campaign using the cartoon character Joe Camel.'These advertisements are thought to influence adolescents' perceptions and behaviour,2 and sponsorship of sports events by tobacco companies may have the same effect.3 We studied the effect of sports sponsorship on children's experimentation with tobacco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 4 publications
1
26
0
Order By: Relevance
“…The effect of sport sponsorship on youth was further demonstrated by Vaidya, Naik and Vaidya (1996) who found a significantly higher prevalence of experimentation with smoking amongst respondents who had watched television coverage of a professional cricket match sponsored by a cigarette brand, than amongst those who had not.…”
Section: Influences On Regulation Of Sport Sponsorshipmentioning
confidence: 99%
“…The effect of sport sponsorship on youth was further demonstrated by Vaidya, Naik and Vaidya (1996) who found a significantly higher prevalence of experimentation with smoking amongst respondents who had watched television coverage of a professional cricket match sponsored by a cigarette brand, than amongst those who had not.…”
Section: Influences On Regulation Of Sport Sponsorshipmentioning
confidence: 99%
“…Sport sponsorship also influences young people's awareness, recall and use of sponsors' products. Sport sponsorship by tobacco companies increases young people's awareness and recall of tobacco brands (Ledwith, 1984;Sparks, 1999) and experimentation with tobacco products (Vaidya, Naik, & Vaidya, 1996). A large longitudinal study found that increased brand awareness of tobacco products in early adolescence heightened risks of becoming a smoker (Lopez et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…While there has been little research to demonstrate the effect of food and beverage sponsorship on children, empirical evidence from consumer studies relating to tobacco and alcohol sponsorship have demonstrated that sponsorship has an impact on product recall and product-related attitudes and behavioural intentions (6) . This body of research has identified that sponsorship increases brand recall (7) , favourable attitudes to brands (8,9) , purchasing behaviours (10) and ultimately product consumption (7) . Evidence that alcohol sponsorship can create positive associations between alcohol and sport has led to calls to also limit this form of sponsorship (11) .…”
mentioning
confidence: 99%